RANCANG BANGUN SISTEM INFORMASI E-MARKETING PADA PT PULAU CAHAYA TERANG - tukino, tukino (Computer Based Information System Journal, 2020)
Current technological developments are increasing, one of which is the development of the internet that is very fast, many companies are starting to offer their products through the internet to maximize their profits, so that competition between companies is getting tighter. PT Pulau Cahaya Terang  is one company that manufactures and sells various types of spring beds and equipment in the city of Batam. The sales system is by the way consumers come directly to the company, contact by telephone, or the company offers products directly through salesmen, the system Used is less effective now, becaUse consumers find it difficult to get the latest information and making an order quickly. For this reason, it is necessary to create a web-based sales information system at PT Pulau Cahaya Terang  so that consumers can easily access product information and can also directly order and pay for products through the website. The method Used is the SDLC Waterfall model which consists of needs analysis, design, programming code, testing, implementation and maintenance. The results of this research are a website-based sales information system that makes it easier for consumers to obtain information and order products, and save employee costs and time